Studi Teknologi Alat Tangkap Jermal Di Desa Kota Pari Kecamatan Pantai Cermin Kabupaten Serdang Bedagai Provinsi Sumatera Utara - Sormin, Palti M; Brown, Arthur; Rengi, Pareng (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted in April 2014 in Kota Pari village Kota Pari sun district Serdang Bedagai regency in North Sumatera Province. This study aims to determine the level of environmental friendliness sembilang gear nets using tuasan, feasibility as well as factors related to the arrest of environmentally friendly technologies. The method used in this study is a survey method with direct observation and interviews and discussions with fisherman. Observation made by FAO (1995) shows that fishing gear including nets sembilang use tuasan into environmentally friendly fishing gear. The results of the feasibility analysic calculations indicate that nets fishing effort Sembilang using tuasan provide benefits for fishermen and deserves to be developed because of the value of BCR (Benefit Cost Ratio) retrieved of 1,19 FRR (Financial Rate of Return) is 0,19 % and PPC (Payback Period of Capital) is 11 years.Keywords : Jermal, Technology, Selectivity, Business Feasibility, Kota Pari